Finite Element Analysis of the Effect of Superstructure Materials and Loading Angle on Stress Distribution around the Implant - Jafari K; Vojdani M; Mahdavi F; Heidary H (Shiraz University of Medical Sciences, 2014)
Statement of Problem: A general process in implant design is to determine the reason of possible problems and to find the relevant solutions. The success of the implant depends on the control technique of implant biomechanical conditions. Objectives: The goal of this study was to evaluate the influence of both abutment and framework materials on the stress of the bone around the implant by using threedimensional finite element analysis. Materials and Methods: A three-dimensional model of a patient's premaxillary bone was fabricated using Cone Beam Computed Tomography (CBCT). Then, three types of abutment from gold, nickel-chromium and zirconia and also three types of crown frame from silver-palladium, nickel-chromium and zirconia were designed. Finally, a 178 N force at angles of zero, 30 and 45 degrees was exerted on the implant axis and the maximum stress and strain in the trabecular, cortical bones and cement was calculated. Results: With changes of the materials and mechanical properties of abutment and frame, little difference was observed in the level and distribution pattern of stress. The stress level was increased with the rise in the angle of pressure exertion. The highest stress concentration was related to the force at the angle of 45 degrees. The results of the cement analysis proved an inverse relationship between the rate of elastic modulus of the frame material and that of the maximum stress in the cement. Conclusions: The impact of the angle at which the force was applied was more significant in stress distribution than that of abutment and framework core materials.